일경일화 민무늬 향 춘란 ‘아리향’ - 박소연(So yeon Park); 김동용(Dong yong Kim); 박영희(Young hie Park); 이주현(Joo hyun Lee); 권순욱(Soon wook Kwon) (Korean journal of breeding, 2018)
Cymbidium goeringii of ‘Arihyang’ was developed for a fragrant Korean Cymbidium variety by Semangeum Bio Center. ‘Arihyang’ was developed from the cross between ‘Daebugui’ as a good fragrant source and ‘SC-005’, a collected Korean Cymbidium collected in 2001, which shows short plant-type and round flower. The selected seed was germinated and cultivated in 2007. Through continuous cultivation and checking the fixed phenotype from 2007 to 2008, the fixed phenotype of none boundary line jade color flower and moderate fragrance was confirmed. In 2010, ‘Arihyang’ was cultivated in field and evaluated the phenotype to be confirmed the fixed phenotype. ‘Arihyang’ has length of 20~25cm plain leaves with dark green color. The flower has a moderate fragrance with jade color. The length and width of flower are 2.5cm, 3cm, respectively. KCI Citation Count: 1